Genomic Comparisons Reveal Microevolutionary Differences in Mycobacterium abscessus Subspecies - Tan, Joon L.; Ng, Kee P.; Ong, Chia S.; Ngeow, Yun F. (Frontiers in Microbiology, 2017)
Mycobacterium abscessus, a rapid-growing non-tuberculous mycobacterium, has been the cause of sporadic and outbreak infections world-wide. The subspecies in M. abscessus complex (M. abscessus, M. massiliense, and M. bolletii) are associated with different biologic and pathogenic characteristics and are known to be among the most frequently isolated opportunistic pathogens from clinical material. To date, the evolutionary forces that could have contributed to these biological and clinical differences are still unclear. We compared genome data from 243 M. abscessus strains downloaded from the NCBI ftp Refseq database to understand how the microevolutionary processes of homologous recombination and positive selection influenced the diversification of the M. abscessus complex at the subspecies level. The three subspecies are clearly separated in the Minimum Spanning Tree. Their MUMi-based genomic distances support the separation of M. massiliense and M. bolletii into two subspecies. Maximum Likelihood analysis through dN/dS (the ratio of number of non-synonymous substitutions per non-synonymous site, to the number of synonymous substitutions per synonymous site) identified distinct genes in each subspecies that could have been affected by positive selection during evolution. The results of genome-wide alignment based on concatenated locally-collinear blocks suggest that (a) recombination has affected the M. abscessus complex more than mutation and positive selection; (b) recombination occurred more frequently in M. massiliense than in the other two subspecies; and (c) the recombined segments in the three subspecies have come from different intra-species and inter-species origins. The results lead to the identification of possible gene sets that could have been responsible for the subspecies-specific features and suggest independent evolution among the three subspecies, with recombination playing a more significant role than positive selection in the diversification among members in this complex.